Proposed mechanisms to expand the base of financial inclusion and access to financial services in Iraq - رشا عودة لفته; سالم عواد حسين (Journal of Madenat Alelem University College, 2019)
Policy makers, governments, international institutions and private sector institutions have become increasingly concerned with the concept of financial inclusion over the past years, with a growing number of studies reviewing the impact of the development of financial inclusion on the economic development process and its contribution to creating comprehensive development and achieving sustainable economic growth. Improving income distribution, increasing women’s empowerment, improving individuals’ risk management capacity, increasing levels of savings and consumption, as well as their positive effects on labor markets and per capita income levels This research aims to reach mechanisms to enhance the financial coverage in Iraq because of its importance in expanding the circle of beneficiaries of financial services, which will contribute to the empowerment of the whole community of financial services and enhance the financial independence of individuals, and achieve sustainable economic development in addition to the optimal use of resources. The search for several proposed mechanisms, mainly the conversion of cash payments to payments through the official accounts and the automation of financial services and increase the use of financial services electronically. And one of the most important recommendations on the CBI to enhance levels of financial inclusion through the transfer of salaries Employees to accounts in official financial institutions, which positively reflects on economic performance, as well as the use of official electronic financial channels helps to ensure that beneficiaries pay regular service bills.